A multi-criteria vertical coordination framework for a reliable aid distribution - Fabiola Regis-Hernández; Jaime Mora-Vargas; Angel Ruíz (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: This study proposes a methodology that translates multiple humanitarian supply chain stakeholders' preferences from qualitative to quantitative values, enabling these preferences to be integrated into optimization models to ensure their balanced and simultaneous implementation during the decision-making process. Design/methodology/approach: An extensive literature review is used to justify the importance of developing a strategy that minimizes the impact of a lack of coordination on humanitarian logistics decisions. A methodology for a multi-criteria framework is presented that allows humanitarian stakeholders' interests to be integrated into the humanitarian decision-making process. Findings: The findings suggest that integrating stakeholders' interests into the humanitarian decision-making process will improve its reliability. Research limitations/implications: To further validate the weights of each stakeholder's interests obtained from the literature review requires interviews with the corresponding organizations. However, the literature review supports the statements in this paper. Practical implications: The cost of a lack of coordination between stakeholders in humanitarian logistics has been increasing during the last decade. These coordination costs can be minimized if humanitarian logistics' decision-makers measure and simultaneously consider multiple stakeholders' preferences. Social implications: When stakeholders' goals are aligned, the humanitarian logistics response becomes more efficient, increasing the quality of delivered aid and providing timely assistance to the affected population in order to minimize their suffering. Originality/value: This study provides a methodology that translates humanitarian supply chain stakeholders' interests into quantitative values, enabling them to be integrated into mathematical models to ensure relief distribution based on the stakeholders' preferences.
Keywords: 650; humanitarian logistics; relief distribution; multi-criteria; response; methodology; vertical coordination